2012
DOI: 10.4067/s0717-95022012000400034
|View full text |Cite
|
Sign up to set email alerts
|

Microarchitecture of the Palatine Tonsil in Sheep (Ovis aries)

Abstract: SUMMARY:The tissue pieces of palatine tonsil were collected from different postnatal age groups of sheep from the Corporation Slaughter House, Perambur, Chennai. The palatine tonsil consisted of a surface epithelium, capsule, tonsillar lobes, crypts, crypt epithelium and tonsillar follicles. The surface epithelium over the palatine tonsil was made up of non-keratinized stratified squamous epithelium in all the postnatal age groups studied. The palatine tonsil was clearly demarcated from the surrounding structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
2
0
0
Order By: Relevance
“…According to Ramos et al, (1992) FDC were fundamental in the development of secondary follicles. All these observations tally with the reports of Halleraker et al, (1990) in goats and Raju et al, (2012) in sheep.…”
Section: Resultssupporting
confidence: 75%
“…According to Ramos et al, (1992) FDC were fundamental in the development of secondary follicles. All these observations tally with the reports of Halleraker et al, (1990) in goats and Raju et al, (2012) in sheep.…”
Section: Resultssupporting
confidence: 75%
“…The tonsillar crypts were lined by a non‐keratinized stratified squamous epithelium in goat. Similar observation was recorded in goat, sheep and ox (Casteleyn et al, 2011; Girgiri & Kumar, 2018; Indu et al, 2018; Kumar et al, 2008; Palmer et al, 2009; Raju et al, 2012). Indu et al (2018) showed that the palatine tonsil of goat has primary and secondary crypts, therefore, it has a more extensive crypt system than that of sheep (Casteleyn et al, 2011).…”
Section: Discussionsupporting
confidence: 79%